Evaluating the potentials of mosque as a tourist attraction place in Malaysian urban context - Nangkula Utaberta; Leong, Yin Chen; M.M. Tahir (Penerbit Universiti Kebangsaan Malaysia, 2021)
The main purpose of this study is to identify the potentials of mosque as tourist attraction place in Malaysia. This study uses case study and empirical study as methodology choosing two mosques from outside the world and in Malaysia as a sample that are tourist attraction spots. In this study, discussion whether mosque should become a tourist attraction place and the factors that make a mosque popular among the tourists was discussed by giving some good examples of selected mosque. It is expected that this study can make the public as well as the officials aware of the tourism potentials of the mosque in Malaysia. This paper also presented the potentials and considerations of selected mosques in managing its tourism function as reference for further development of Islamic Architecture (in this case Mosques) in Malaysia.